Human Resource Practices and Employees’ Performance in Higher Education Institutions in General Santos City - De Vera, Freden S.; Echalar, Lovely V. (International Journal of Research in Interdisciplinary Studies, 2025)
This paper investigated the association between HR practice and employee performance in the selected private HEIs in General Santos City. With the idea of how the HRM practices— recruitment and selection, training and development, performance management, compensation and benefits— being implemented would affect employees’ performance relative to the prevailing conditions of utilization of HR practices (extent), timing of implementation (timelessness), timely completion of day-to-day activities (timeliness) the study provided and tested for research measures. Simple random technique was used to select 265 respondents that participated through structured questionnaires. The study also explored the role of individuals' demographic characteristics (age, sex, position, salary, education level, years of service) on HR practices and performance outcomes. Statistical analysis with the help of Spearman’s rho, Kruskal-Wallis and Mann-Whitney U tests demonstrated that well implemented HR practices were significantly correlated to higher employee performance. Variations in the extent and quality of implementation of HR practice are apparent among demographic groups. Implications The results highlight the broader importance of strategic HR practices on workplace productivity and organizational achievement. Practical implications: HR interventions should be personalized, supportive profanity-based technologies, and transparent and inclusive recruitment and training programs. The paper provides insights into HRM in higher education and provides a platform for further organizational development and academic research.